Measuring Public Opinion Regarding Peaceful Solution of Palestine Issue: An Experimental Study of University Students in Pakistan, Iran and United Arab Emirates (Global Journal of Human-Social Science, 2014)
Abstract not found
Keywords: uae; i-p union; religiosity; eu; state of judea